Rubicon - Dewes, J. S. (Crucible cycle novel, 2023)
"Sergeant Adrienne Valero wants to die. She can't. After enduring a traumatic resurrection for the ninety-sixth time, Valero is reassigned to a special forces unit and outfitted with a cutting-edge virtual intelligence aid. They could turn the tide in the war against intelligent machines dedicated to the assimilation, or destruction, of humanity. When her VI suddenly achieves sentience, Valero is drawn into the machinations of an enigmatic major who's hell-bent on ending the war-by any means necessary"--